2019
DOI: 10.3390/ijerph16214089
|View full text |Cite
|
Sign up to set email alerts
|

Stratified Diabetes Mellitus Prevalence for the Northwestern Nigerian States, a Data Mining Approach

Abstract: An accurate classification for diabetes mellitus (DBM) allows for the adequate treatment and handling of its menace, particularly in developing countries like Nigeria. This study proposes data mining techniques for the classification and identification of the prevalence of diagnosed diabetes cases, stratified by age, gender, diabetic conditions and residential area in the northwestern states of Nigeria, based on the real-life data derived from government-owned hospitals in the region. A K-mean assessment was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…1) is consistent with the result of Shittu et al (2017), who reported the prevalence of 36-60-year age class among type 2 diabetics in southwest Nigeria. Muhammad et al (2019) also reported a similar result to the current study in which the age group 50-69 years was the most susceptible group to T2DM in the northwest of Nigeria.…”
Section: Discussionsupporting
confidence: 90%
“…1) is consistent with the result of Shittu et al (2017), who reported the prevalence of 36-60-year age class among type 2 diabetics in southwest Nigeria. Muhammad et al (2019) also reported a similar result to the current study in which the age group 50-69 years was the most susceptible group to T2DM in the northwest of Nigeria.…”
Section: Discussionsupporting
confidence: 90%
“…Type 2 DM is a chronic disease that cannot be fully cured, leading to increasing prevalence every year 5 . Study by Dante et al (2020) expressed that without proper treatment, diabetes patients in general have worse quality of life than non-patients due to the risk of complications 6 .…”
Section: Original Articlementioning
confidence: 99%
“…BMI was measured as body weight, separated by height squared into meters, and BMI (≥25) was defined as overweight. These five attributes were taken into account from our previously reported prevalence research [ 23 , 27 , 28 , 29 , 35 , 36 ]. Furthermore, the characteristics of smoking (yes or no) were applied to this study because smoking has been a significant factor in human depression or distress in clinical trials and psychiatric expertise [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The IDF cited a huge number of deaths associated with diabetes in the literature. The findings in [27][28][29][30][31] determine the factors associated with the prevalence of diabetes in Nigeria for primary health education; however, for the factors of distress and depression among Nigerian diabetic patients, this study is novel. It motivates us with significance to the clinical implications.…”
Section: Introductionmentioning
confidence: 99%